A systematic review on the influence of the horizontal distance between two adjacent implants inserted in the anterior maxilla on the inter‐implant mucosa fill. Issue Volume 29:Issue S15(2018) (2nd March 2018) - Ramanauskaite, Ausra; Roccuzzo, Andrea; Schwarz, Frank
Abstract: Objectives: To address the following focused question: "Does the horizontal distance between two adjacent implants inserted in the anterior maxilla affect the inter‐implant mucosa fill?". Material and Methods: A comprehensive literature screening was performed in MEDLINE and Cochrane databases from January 1, 2000 until July 1, 2017. Clinical human studies including ≥10 patients treated with at least two adjacent implant‐supported crowns in the anterior maxilla with a minimum of 12 months of follow‐up were searched. Studies reporting on inter‐implant mucosa fill in relation to the radiographic horizontal distance between the two adjacent implants were included. The reporting of this systematic analysis adhered to the Preferred Reporting items for Systematic Review and Meta‐analyses (PRISMA) statement. Results: The initial search resulted in 208 publications. From 13 full‐text articles reviewed, 4 were included in the final analysis. Depending on the reference points used, the horizontal inter‐implant distance ranged between 2.01 and 4.0 mm. In 21 to 88.5% of the cases, inter‐implant‐mucosa filled more than half of the inter‐implant space. When interpreting results of inter‐implant mucosa fill, time of implant placement (immediate or delayed) and restoring (immediate or conventional) were taken into consideration. A tendency towards incomplete inter‐implant mucosa fill at a distance of <3 mm was noted in the 3 included papers. One of the studies found this trend to be statistically significant ( p = .008). Conclusions: Based on the available evidence, it is not possible to define a precise threshold for the optimal horizontal distance between two adjacent implants.